Lip And Palate Reconstruction On Median Cerebrofacial Malformation Patient - Anindhawati, Nur; Kreshanti, Prasetyanugraheni; Handayani, Siti; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: Median cerebrofacial malformations are developmental anomalies of the midline brain and facial structures. The clinical manifestations ranges from holoprosencephaly with agenesis of central facial structures, to those seen in median facial dysplasia. Patients who survive are usually born with severe functional limitation and die during infancy. Nowadays, with improved perinatal care, patient with severe midline craniofacial abnormalities can be expected to live longer. The purpose of this paper is to show how reconstruction of the lip and palate on patient with median cerebrofacial malformation is done. Patient and Method: Reporting 2 cases of child with cleft median cerebrofacial malformations. First case was a 2 year-old child with complete median cleft lip and palate. Clinical examinations and CT scan revealed a holoprosencephaly. She was also diagnosed with laryngomalacia. The second case was a 4 month-old patient with median cleft lip and palate also microcephaly. We performed labioplasty in both patients and did the palatoplasty in the first patient. Result: Both cases showed no sign of complication after the operation. They both discharged one day after the operation. The first patient reported dead 1 week after the surgery at home. The cause was unknown. Discussion: Disturbed maxillary growth is postulated to be caused by the manipulation and suturing of the maxillary vomer, and scarring of the dentoalveoli post-surgery. Another contributing factor is the intrinsic tissue deficiency. Summary: With proper perinatal care and holistic teamwork that expand the survival rate we expect those with the best prognosis deserve to appear as normal as possible. Keywords: Holoprosencephaly, median facial dysplasia, median cleft lip and palate